Documentation of priority CSA practices and systems for NDC and NAP implementation in Vietnam - Northern Mountainous Agriculture and Forestry Science Institute (2018)
Towards large scale adoption of CSA practice, not only in CSVs but also in the whole Vietnam, CCAFS has provided support to documentation and dissemination of information on CSA practices and systems having values for the implementation of Nationally Determined Contributions (NDC) and the National Adaptation Plan (NAP) in different locations in the country. This effort involves: defining the suitability levels of each priority CSA practice of system for large-scale in each location (province or agro-ecological zones); and combining information into a database to serve as an evidence-base for 64 provinces and cities in Vietnam to develop their CSA development plans. Preliminarily, in total, 57 existing CSA practices and systems in Vietnam were identified as priority for promoting adoption by provinces in implementing NAP and NIDC. These could be grouped into (i) pest control and production of quality products, (ii) protection and sustainable use of cultivated land and water resource, (iii) agroforestry and integrated cropping systems, (iv) paddy rice production, (v) livestock and (vi) aquaculture.